No “Self” Advantage for Audiovisual Speech Aftereffects - Modelska, Maria; Pourquié, Marie; Baart, Martijn (Frontiers in Psychology, 2019)
Although the default state of the world is that we see and hear other people talking, there is evidence that seeing and hearing ourselves rather than someone else may lead to visual (i.e., lip-read) or auditory ‘self’ advantages. We assessed whether there is a ‘self’ advantage for phonetic recalibration (a lip-read driven cross-modal learning effect) and selective adaptation (a contrastive effect in the opposite direction of recalibration). We observed both aftereffects as well as an on-line effect of lip-read information on auditory perception (i.e., immediate capture), but there was no evidence for a ‘self’ advantage in any of the tasks (as additionally supported by Bayesian statistics). These findings strengthen the emerging notion that recalibration reflects a general learning mechanism, and bolster the argument that adaptation depends on rather low-level auditory/acoustic features of the speech signal.